Associations Between Infant Negative Affect and Parent Anxiety Symptoms are Bidirectional: Evidence from Mothers and Fathers - Brooker, Rebecca J.; Neiderhiser, Jenae M.; Leve, Leslie D.; Shaw, Daniel S.; Scaramella, Laura V.; Reiss, David (Frontiers in Psychology, 2015)
Little is known about child-based effects on parents’ anxiety symptoms early in life despite the possibility that child characteristics may contribute to the quality of the early environment and children’s own long-term risk for psychological disorder. We examined bidirectional effects between parent anxiety symptoms and infant fear-based negative affect using a prospective adoption design. Infant fear-based negative affect and adoptive parent anxiety symptoms were assessed at child ages 9, 18, and 27 months. Birth parent negative affect was assessed at child age 18 months. More anxiety symptoms in adoptive parents at child age 9 months predicted more negative affect in infants 9 months later. More infant negative affect at child age 9 months predicted more anxiety symptoms in adoptive parents 18 months later. Patterns of results did not differ for adoptive mothers and adoptive fathers. Birth parent negative affect was unrelated to infant or adoptive parent measures. Consistent with expectations, associations between infant negative affect and rearing parents’ anxiety symptoms appear to be bidirectional. In addition to traditional parent-to-child effects, our results suggest that infants’ characteristics may contribute to parent qualities that are known to impact childhood outcomes.